BEING SECURITY CONSCIOUS: ANALYSING SOCIAL MEDIA SECURITY-ORIENTED MESSAGES IN CREATING SECURITY ALERTNESS IN IMO STATE, NIGERIA - Etumnu, Emeka Williams; Nwosu , Lauretta Chinenye; Jumbo , Cynthia N.; Ogu , Clinton Chukwuma; Amadi, Chukwudumebi Kelechi (Journal of Sociology: Bulletin of Yerevan University, 2025)
This study investigated the role of social media in creating security alertness in Imo State, Nigeria. The research design for this study was a mixed-methods approach employing survey and content analysis. The data indicated that both Imo State Blog and Imo State New Media Facebook pages featured security-related information but with variable rates. Imo State Blog had 11 security-related postings within one year, whereas Imo State New Media published merely 7 posts over the same period. Also, findings suggested that the majority of people had frequent exposure to security-related posts on social media platforms and were aware of security alertness messages sent through these platforms. It was concluded that social media plays an essential role as a medium for enhancing security alertness and encouraging community safety behaviours within the region.